Development of E-Comic Assisted LKPD in the PBL Model to Improve Mathematical Literacy of Grade VII Students - Berlian Ifadariyanti; Wakhid Fitri Albar (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2026)
This study aims to develop Student Worksheets (LKPD) assisted by e-comics in the Problem Based Learning (PBL) model to improve the mathematical literacy of seventh grade students. The background of this study is the low mathematical literacy skills of students in data and diagram materials that require the skills of understanding, interpreting, and using mathematical concepts in everyday contexts. The research method used was Research and Development (R&D) with a 4-D development model (Define, Design, Develop, Disseminate). The research subjects were seventh-grade students at a junior high school in Klaten. The instruments used included expert validation sheets, student response questionnaires, and mathematical literacy tests. The results showed that the e-comic-assisted LKPD developed had a validity level of 92.02% in terms of media and 92.76% (highly valid) in terms of material. The practicality test conducted by teachers yielded a result of 86.25% (practical), while the practicality test conducted by students yielded a result of 83.38% (practical. The average Gain Score obtained was 0.59, which falls into the effective category. Furthermore, the classical mastery results were in the very high category. Thus, e-comic-assisted worksheets in the PBL model are effective in improving mathematical literacy. Therefore, these worksheets are suitable for use as an innovative learning resource to support contextual, interesting, and student-centered mathematics learning.